Interactive Multimedia With a Contextual Approach to Improve Learning Outcomes in The Pancasila Education Subject in Grade V - Hudadiyatul Ummah; I Nyoman Jampel; I Made Tegeh (Mimbar Pendidikan Indonesia, 2025)
The lack of application of a contextual approach in learning Pancasila Education in class V causes the material to be difficult to understand for students, so it is necessary to develop interactive multimedia that can link concepts with real life. This study aims to analyze the effectiveness of the contextual approach in increasing students' interest in learning, active involvement, and conceptual understanding of Pancasila values to create a more meaningful and enjoyable learning experience. This type of research is development research with the ADDIE model, which includes five systematic stages. The results of this study indicate that (1) The design process of this interactive multimedia development was developed through the ADDIE model stage, which consists of five stages, namely the analysis, design, development, implementation and evaluation stages; (2) Validity consists, of expert validity tests and product trials. The results of the expert validity test: (a) learning material content expert test, (b) learning design expert test, and (c) learning media expert test are very good qualifications. Product trial results: (a) individual trials, (b) small group trials, and (c) field trials; (3) Practicality test by teachers obtained very good qualifications; (4) The effectiveness of interactive multimedia is seen from the difference in the average pre-test 38.23 and post-test 87.5. The post-test value is above the KKTP; it is concluded that interactive multimedia is effective for teaching and learning.